THE CAUSES, EXTENT AND EFFECTS OF MEDICO-LEGAL CLAIMS ON HEALTHCARE DELIVERY IN SOUTH AFRICA - Nduduzo NDEBELE (Social Sciences and Education Research Review)
South Africa's healthcare system is on the cusp of a perfect storm that has the potential to paralyze service delivery, due to the increasing costs of providing healthcare services and the increase in medical malpractice litigations. Thus, the paper investigates the extent and effects of medico-legal claims on healthcare service delivery and the underlying factors causing the increase in the health sector. The paper revealed that staff shortages, decline in professionalism, poor record-keeping, poor health systems are among the factors contributing to high medical malpractice litigations. The paper concluded that for the benefit of healthcare providers and patients, medical malpractice grievances should be settled in a non-adversarial manner outside of the courts it poses a serious threat to the survival of both the public and private health system.